Formulation and In Vitro Evaluation of Fig Leaf (Ficus carica L.) Ethyl Acetate Extract Transdermal Patch as a Candidate for Wound Healing Application - Ratih Aryani; Safira Qamarani; Hanifa Rahma; Taufik Muhammad Fakih (Direktorat Politeknik Kesehatan Makassar, 2026)
Wound healing can be enhanced through both non-pharmacological and pharmacological approaches. Non-pharmacological methods include proper wound cleaning and dressing, while pharmacological strategies utilize antiseptics and synthetic antibiotics to prevent infection. Recently, natural compounds such as Ficus carica L. leaves, rich in flavonoids, have gained attention for their wound-healing potential. Flavonoids play a crucial role in accelerating wound contraction, enhancing collagen deposition, and promoting granulation tissue formation. This study aimed to formulate and evaluate a wound-healing patch incorporating the ethyl acetate extract of Ficus carica L. leaves, obtained via multistep maceration. The total flavonoid content (TFC) of the extract was 89.299 ± 0.14 mgQE/g. The patch was developed using the solvent casting method with HPMC K100M as the polymer matrix and propylene glycol as a plasticizer. The optimized formulation, containing 5.6% ethyl acetate extract (equivalent to 50 mg quercetin), met key evaluation criteria, exhibiting a uniform structure without wrinkling, a thickness of 1.0 ± 0.2 mm, a pH of 5, and a folding endurance of >200 cycles. In vitro permeation studies demonstrated effective active compound penetration, with a cumulative quercetin permeation of 21.76% within 180 minutes. The flux profile revealed an initial burst release followed by a transition toward controlled diffusion behavior, which is characteristic of HPMC-based monolithic matrices.